Enhancing the Profitability of Manufacturing Firms through the Transfer Pricing Policies in Nigeria - Olayeye, Aduwo Olola; Fajuyagbe, Bamikole Samson; Aduwo, Ayomikun Elizabeth (The Journal of Accounting and Management, 2023)
This study examined the enhancing the profitability of manufacturing firms in Nigeria through the transfer pricing policies. The study covered ten years from 2013 to 2022 and sampled twelve (12) companies engaging the production of goods across the country based on the available data. The study used secondary data to source for data from the financial statements of the sampled companies. The data collated were estimated using panel regression models. The study found that the coefficient (0.582779) of market-based transfer price of manufacturing firms in Nigeria positively and significantly (p=0.0396<0.05) impact the profitability, and also the coefficient (0.582779) of cost-based transfer price of the firms positively and significantly (p=(p=0.0408<0.05)) impact the firms’ profitability. The study concluded that transfer pricing policies positively impact the profitability of manufacturing firms in Nigeria.